The Influence of Service Quality on Clients’ Satisfaction and Its Effect on Their Loyalty at PT Bank Aceh, Medan Branch - Budi Irwansyah (Universitas Negeri Medan, 2018)
PT. Bank Aceh, Medan Branch, undergoes the decrease in its clients’ loyalty which indicated by the increase in non-active clients in the period of 2011-2015. The objective of this research was to find out and analyze the influence of Service Quality on Clients’ satisfaction and its effect on their loyalty at PT. Bank Aceh, Medan Branch. The data were gathered by conducting descriptive quantitative survey and distributing questionnaires to 94 respondents and analyzed by using path analysis. The result of the research showed that,simultaneously, tangibles, reliability, responsiveness, assurance, and empathy had positive and significant influence on clients’ loyalty. Partially, tangibles had positive and significant influence on clients’ loyalty, reliability had positive and significant influence on clients’ loyalty, responsiveness had positive and significant influence on clients’ loyalty, assurance did not have any positive and significant influence on clients’ loyalty, and empathy had positive and significant influence on clients’ loyalty at PT. Bank Aceh, Medan Branch. Clients’ satisfaction had positive and significant influence on clients’ loyalty at PT. Bank Aceh, Medan Branch. Tangibles, reliability, responsiveness, assurance, and empathy directly and indirectly had positive influence on clients’ loyalty through clients’ satisfaction at PT. Bank Aceh, Medan Branch